PENGARUH HARGA MINYAK, EMAS, BATU BARA TERHADAP IHSG 2015–2024 - Ayu Rismawati; Habibah (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study analyzes how changes in oil, gold, and coal prices affect the Indonesia Composite Index (IHSG) between 2015 and 2024, focusing on the impact of global commodity trends on the country’s stock market performance. Using a quantitative approach with multiple linear regression and secondary data from Investing.com and the Indonesia Stock Exchange, the research provides a reliable examination of these relationships. The results demonstrate that fluctuations in oil, gold, and coal prices have a notable positive effect on the IHSG, both individually and collectively. With an R² value of 88%, these variables account for the majority of the index’s movements, while the remaining 12% is influenced by other external factors, highlighting the strong role of commodity price changes in the Indonesian financial market.